Frontispiece: Relativistic DFT Calculations of Hyperfine Coupling Constants in 5d Hexafluorido Complexes: [ReF6]2− and [IrF6]2−. Issue 20 (10th April 2018) - Haase, Pi A. B.; Repisky, Michal; Komorovsky, Stanislav; Bendix, Jesper; Sauer, Stephan P. A.
Abstract : Choosing the appropriate relativistic method for DFT calculations on compounds containing heavy elements: The ZORA and the 4‐component DKS methods were used for calculations of the hyperfine coupling constants of Re IV and Ir IV in their hexafluorido ions. A perturbative treatment of spin–orbit coupling (LR ZORA) works well for [ReF6 ] 2− but fails for [IrF6 ] 2− whereas DKS works for both systems. For more information, see the Full Paper by S. P. A. Sauer et al. onpage 5124 ff.